Magical Realism in Contemporary Indonesian Literature: An Exploration of the Value of Education in a Fantasy World - Arviah Putri Ayuningtyas; Onok Yayang Pamungkas (Athena: Journal of Social, Culture and Society, 2024)
The purpose of this study is as an effort to interpret the short story Peminspin Gelap by Intan Pramataditha in the perspective of magical realism. The value of education is also present as one of the aspects studied because it can provide new knowledge for readers and is considered important to learn. The approach used is to use qualitative methods that focus on semiotics, content analysis, and hermeneutics. The source of the data was obtained from the main object of this study, namely the short story book Peminspin Gelap by Intan Paramaditha. Other data used to support this research relate to magical realism such as book references, some relevant research and electronic journals taken from the internet. Data collection is carried out by reading and recording techniques. The results of this research can be found data from the representation of magical realism in the short story Dark Spinner by Intan Paramadhita. First, magical realism data was found based on the meanings and symbols of images on the cover of the short story anthology book Female Magic, and the cover of the short story Dark Spinner pen.  Then, data were obtained from the analysis of story texts based on Wendy B. Faris's theory, namely: (1) irreducible elements were found two data; (2) the phenomenal world (Phenomenal World) found two data; (3) Unsettling doubt found four data; (4) Merging realms found one data. Then, the value of education was found in the short story Dark Spinner by Intan Paramadhita, namely the value of religious education